Physical Exercise To Prevent Knee Osteoarthritis In Pandean Village, Dongko District, Trenggalek Regency - Natasha Alfira Dhea Novita; Dyah Ulhaq Surya Athory; Naufal Aria Waskita; Ferry Andrias Fathul Bahroini; Rara Ngesthi Retna Ningrum; Risma Karlina Prabawati; Maryam Abdullah (DokTIn MEDIKA Jurnal Pengabdian Masyarakat, 2025)
Osteoarthritis is the most common type of arthritis. Knee osteoarthritis is one of the main causes of disability. This degenerative and progressive joint disease affects approximately 250 million people worldwide. Pain, tenderness and decreased joint range of motion as well as joint stiffness are symptoms that can occur in osteoarthritis sufferers. The prevalence of this disease increases with age. Until the age of 45, knee osteoarthritis affects more men than women, but after the age of 45 the opposite happens. Apart from age and gender, individuals who often do certain physical activities for a long time while doing their work, such as kneeling, squatting, climbing stairs, standing for long periods and lifting heavy weights, can increase the risk of developing osteoarthritis. The aim of this service is to prevent the occurrence of genu osteoarthritis in elderly posyandu participants in Pandean Village, Dongko District, Trenggalek Regency through education regarding genu osteoarthritis. Socialization regarding genu osteoarthritis which was delivered in the form of definition, causes, risk factors, therapy and prevention was given to the elderly. The results of this service activity are increasing the elderly's knowledge about the condition of genu osteoarthritis, and being able to carry out physical exercise as an effort to prevent the incidence of osteoarthritis in Pandean Village, Dongko District, Trenggalek Regency